Pengaruh Kecukupan Modal Dan Risiko Kredit Terhadap Profitabilitas Dengan Cadangan Kerugian Penurunan Nilai Sebagai Variabel Moderasi Pada Sektor Perbankan di Indonesia Pasca Penerapan PSAK 71 - Septiya Vemila Putri; Achmad Fauzi; Wahyu Lestari (Business Management, 2026)
This study examines and analyzes the allowance for impairment losses as a moderating effect of the capital adequacy ratio and non-performing loans on profitability in the banking sector in Indonesia after the implementation of PSAK 71. Data collection in this study comes from the Financial Services Authority (OJK). The population in this study is national private conventional general banking companies registered with the OJK in 2021 - 2024. The sample in this study was 164 data selected through a purposive sampling method. This study uses a panel data regression analysis technique processed using the EViews 11 application with the selected regression model being a random effect model. The results of the study indicate that (1) capital adequacy does not affect profitability, (2) credit risk affects profitability, (3) partially the capital adequacy ratio and non-performing loans affect profitability, (4) the allowance for impairment losses is able to moderate the effect of the capital adequacy ratio on profitability and (5) the allowance for impairment losses is able to moderate the effect of non-performing loans on profitability. This study clarifies that the allowance for impairment losses after the implementation of PSAK 71 is able to moderate the influence of capital adequacy and credit risk on banking profitability.